(untitled) (Journal of Nepal Geological Society, 2015)
The Barind Tract is an elevated Pleistocene Terraces (about 11-48 mamsl) in northwestern Bangladesh and is widely accepted Tract to have been evolved from tectonic upliftment and /or exists as an erosional geomorphic feature. Some part of the Barind Tract bears the characteristics of morphological origin but some areas are providing evidences of tectonic upliftment. The present study is an attempt to interpret the morphological characteristics of the rivers in the area and tried to unveiling the processes that are responsible for the evolution of the Tract. River morphology are interpreted from satellite images and field mapping and are used to relate neotectonic activities occurred in the area. The river forms U-shaped valleys in floodplain areas whereas these are V-shaped within the Barind Tract. The rivers and valleys on the Tract are also comparatively more straight, incised and entrenched, and rivers are tightly meandered, more localized, form paired and unpaired terraces, and antecedent in nature, whereas, the rivers in the floodplain are either meandering, braided or anastomosing drainage channels. Along the boundary between Barind and floodplain the rivers form asymmetric valley with steeping bank along the tract sides. The width/ depth (W/D) ratios of these rivers are much lower within or near to the Tract than the nearby floodplain. The rivers fl owing from the Himalayas change their morphology, trend, nature etc. near and within the Tract. Some of the N-S fl owing rivers turned towards southeast and southwest directions to maintain slope of the uplifted Tract. These are the indication of structural control of these rivers as well as the tectonic origin of the Barind Tract rather than only geomorphic origin. Earthquakes in this region in the recent past also support the same view about structural control and neotectonic activities.